Makna Pesan Sosial dalam Iklan Layanan Masyarakat “Stereotip Z”: Sebuah Kajian Semiotika Riffaterre - Budi Santoso; Andi Halang Lewa (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
Abstract Public Service Advertisements are non-commercial advertisements that aim to sell ideas for the benefit of public service. The message of Public Service Advertisements contains suggestions and persuation to the public to take an action that changes their